1997
DOI: 10.1111/j.1398-9995.1997.tb02549.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and antigenicity of a partially hydrolyzed cow's milk infant formula

Abstract: We evaluated the immunogenicity and antigenicity of a formula based on partially hydrolyzed cow's milk whey protein in infants at risk of atopy and in controls. Total IgE and specific IgE, IgG, and IgG4 subclass antibodies against egg albumin and cow's milk alpha-lactalbumin, casein, and beta-lactoglobulin were measured by radioimmunoassay of cord blood and of peripheral blood at 5 days and 6 months of life in five groups of infants: 16 breast-fed infants at risk of atopy (group 1), 21 partially hydrolyzed whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 25 publications
(6 reference statements)
3
38
0
Order By: Relevance
“…However, our results showed that the significantly less number of atopic dermatitis occurred in high risk infants fed with the partially hydrolyzed formula compared with the standard cow's milk formula, although this study did not compare the effects between the extensively hydrolyzed formula and the partially hydrolyzed formula. This data support the previous reports (4,8,13,14), in which the partially hydrolyzed formula prevented the development of either atopic disease or cow's milk allergy. In addition, no difference in the rate of growth was observed between the PHF and SF group.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, our results showed that the significantly less number of atopic dermatitis occurred in high risk infants fed with the partially hydrolyzed formula compared with the standard cow's milk formula, although this study did not compare the effects between the extensively hydrolyzed formula and the partially hydrolyzed formula. This data support the previous reports (4,8,13,14), in which the partially hydrolyzed formula prevented the development of either atopic disease or cow's milk allergy. In addition, no difference in the rate of growth was observed between the PHF and SF group.…”
Section: Discussionsupporting
confidence: 82%
“…Because the partially hydrolyzed formula is cheaper and more palatable than the extensively hydrolyzed formula, it was introduced for feeding high-risk infants who cannot tolerate the extensively hydrolyzed formula to prevent the development of atopic disease. The preventive effect of the partially hydrolyzed formula is still controversial because it contains a significant number of peptides with relatively high molecular weight compared with the extensively hydrolyzed formula (2)(3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that raised food‐specific IgG1 could represent a predictive biomarker for future allergic disease, in high‐risk infants. This may have been mediated by the hydrolysis rather than prebiotics because hen's egg‐specific IgG1 was not altered, and others have also reported that hydrolysis can reduce cow's milk‐specific IgG1 25. The increased pDC and Treg percentage in infants receiving pHF‐OS is consistent with increased tolerogenic immune responses, as both cell types play an important role in programming and regulating immune responses 26 and reducing the risk of Th2‐mediated allergic immune responses 27.…”
Section: Discussionmentioning
confidence: 85%
“…However, using the criteria of a 2006 Cochrane review, 41 only 14 randomized or quasirandomized (eg, using alternation) trials in term infants compared the use of partially or extensively hydrolyzed formula with the use of human milk or an adapted cow milk formula. [42][43][44][45][46][47][48][49][50][51][52][53][54][55] All of these trials have followed up with at least 80% of study participants. It is important to note that none of these studies reported any adverse effects, including any adverse effect on infant growth.…”
Section: Role Of Hydrolyzed Formula On the Development Of Atopic Diseasementioning
confidence: 99%